2021
DOI: 10.3389/fpsyg.2021.569380
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Absolute Language and Moral Reasoning on Endorsement of Moral Foundations

Abstract: Morality – the subjective sense that humans discern between right and wrong – plays a ubiquitous role in everyday life. Deontological reasoning conceptualizes moral decision-making as rigid, such that many moral choices are forbidden or required. Not surprisingly, the language used in measures of deontological reasoning tends to be rigid, including phrases such as “always” and “never.” Two studies (N = 553) drawn from two different populations used commonly used measures of moral reasoning and measures of mora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In their article, the Interplay between Absolute Language and Moral Reasoning on Endorsement of Moral Foundations, Blankenship et al (2021) suspected that the language of scale items may have influenced the results of their study. They point toward a majority of topics used to assess moral reasoning to be closely related to the Care/harm factor of moral foundations with topics or issues including killing, euthanasia, betrayal and deception.…”
Section: Overall Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their article, the Interplay between Absolute Language and Moral Reasoning on Endorsement of Moral Foundations, Blankenship et al (2021) suspected that the language of scale items may have influenced the results of their study. They point toward a majority of topics used to assess moral reasoning to be closely related to the Care/harm factor of moral foundations with topics or issues including killing, euthanasia, betrayal and deception.…”
Section: Overall Discussion and Limitationsmentioning
confidence: 99%
“…This includes the debate over construct definitions of empathy and compassion, ( Cuff et al, 2016 ; Bloom, 2017 ; Hall and Schwartz, 2019 ). Still further questions arise on the validity of our assessments in general, and how the language used in these assessments may contribute to our results, ( Blankenship et al, 2021 ). But perhaps the most important question pertains to our understanding of how VR experiences can possibly contribute to pro-social behavior.…”
Section: Overall Discussion and Limitationsmentioning
confidence: 99%
“…For further studies, we placed the English versions of episodes set in OSF that were marked to the episodes that included Japanese and/or Asian-specific names and rules. Several previous studies suggested that the moral judgments are affected by wordings (e.g., “always”) and framings 49 52 . The present study did not confirm whether the episodes had clear thematic and linguistic distinctions between moral categories.…”
Section: Discussionmentioning
confidence: 99%